Synthetic Minority Over-Sampling Technique (SMOTE) and Logistic Model Tree (LMT)-adaptive boosting algorithms for classifying imbalanced datasets of nutrient and chlorophyll sufficiency levels of oil palm (Elaeis guineensis) using spectroradiometers and unmanned aerial vehicles - Amirruddin, Amiratul Diyana; Muharam, Farrah Melissa; Ismail, Mohd Hasmadi; Tan, Ngai Paing; Ismail, Mohd Firdaus (Elsevier, 2022)
The conventional method to quantify leaf biochemical properties (nutrients and chlorophylls) is tedious, labour-intensive, and impractical for vast oil palm plantation areas. Spectral analysis retrieved from a spectroradiometer and an unmanned aerial vehicle (UAV) and imbalanced approaches such as the Synthetic Minority Over-sampling TEchnique (SMOTE) and machine learning have given promising results for monitoring plant biochemical properties. However, the integration of these methods is not widely explored for oil palm. There are three primary aims of the current study. We evaluate the effectiveness of the integration of SMOTE, Logistic Model Tree (LMT), and Adaptive Boosting (AdaBoost) to address data imbalance problems for the assessment of the oil palm nutrients and chlorophylls status. The performance of the raw band and vegetation index (VI) extracted from the UAV in assessing leaf biochemical properties of mature oil palms is also addressed. Finally, we compare the competency of the spectral model retrieved from the spectroradiometer and UAV. In the study, nitrogen (N) treatments varying between 0 and 6 kg palm−1 were applied to mature Tenera palms. The integration of SMOTE with LMT and AdaBoost (LMT-SMOTEBoost) outperformed other approaches in classifying the leaf biochemical sufficiency status of mature oil palm. The VIs outperformed the raw band in discriminating the leaf biochemical properties at the canopy level. Both leaf and canopy spectral models obtained from spectroradiometer and UAV were comparable and produced good performance with balanced accuracy (BAcc) above 0.77. Using these techniques may provide palm oil plantation owners with a cost-effective way to monitor nutrient levels in palms more efficiently and comprehensively to ensure greater harvests and tree health.